2010
DOI: 10.4049/jimmunol.1000221
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Exposure to HIV Induces Virus-Specific T Cell Responses and Immune Activation in Exposed HIV-Seronegative Individuals

Abstract: HIV-specific T cells response and T cell activation are frequently seen in exposed seronegative individuals (ESN). In this study, we report HIV-specific response and level of T cell activation in ESN partners of HIV-infected patients presenting low or undetectable levels of HIV-RNA. We evaluated 24 HIV-serodiscordant couples. ESN were classified into three categories of exposure to HIV (very low, low, and moderate-high), considering levels of HIV-RNA in their infected partner and frequency of sexual high-risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 40 publications
3
29
0
1
Order By: Relevance
“…More specifically, triple infected PWID had lower percentages of CD4 + cells and higher percentages of CD8 + cells and immune activation markers than HIV negative PWID groups, which was a finding similar to that for hetero-and homosexually infected HIV-positive individuals without known coinfections (21,25,35). Although we were unable to assess the distinct effects of HIV due to a lack of mono-infected subjects among the PWID, the changes in the T cell distribution among the Only values with significant differences between cell populations are presented.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…More specifically, triple infected PWID had lower percentages of CD4 + cells and higher percentages of CD8 + cells and immune activation markers than HIV negative PWID groups, which was a finding similar to that for hetero-and homosexually infected HIV-positive individuals without known coinfections (21,25,35). Although we were unable to assess the distinct effects of HIV due to a lack of mono-infected subjects among the PWID, the changes in the T cell distribution among the Only values with significant differences between cell populations are presented.…”
Section: Discussionsupporting
confidence: 73%
“…To the best of our knowledge, this is the first study to demonstrate altered T cell subset distribution ( + T cell and macrophage shifts in response to opioid exposure (3,33) and in vitro studies have found opioids to have additional effects that lead to an increase in the expression of the HIV coreceptor CCR5 (19,24,32,33). The increased CD38 and or HLA-DR, together with the differences in the multiple cell populations of the PWID found in the present study, could be explained by various factors, such as the abiotic substances injected, to an individual's systemic circulation, an unproductive infection with HIV, or the two hepatitis viruses (4,21,25,26). Overall, the changes seen in the triple negative PWID may have been caused by opioids or viral exposure; nevertheless, the immune system is already altered as a consequence of IDU, even when individuals remain seronegative to HIV, HBV, and HCV.…”
Section: Figmentioning
confidence: 52%
“…Subsequent reports confirmed the presence of antigen-specific T cell responses to HIV-1 in HESN subjects while characterizing the functional and proliferative capacity of HIV-specific T cells in these subjects [7,[25][26][27]. Genetically, both major histocompatibility complex (MHC) class I [28] and human leucocyte antigen (HLA) class II [29] alleles have been associated with a reduced risk of infection with HIV-1.…”
Section: Hiv-1-specific T Cell Responses In Hesn Subjectsmentioning
confidence: 90%
“…A systematic review of these studies suggests that natural resistance to HIV infection in highly exposed individuals is mediated by multiple mechanisms, conferring on them an ''immunologic advantage'' that may be related to innate and/or adaptive immune systems. 66,67 Although offering only a partial explanation to the natural resistance to HIV infection, 68 observations in female sex workers in Nairobi with frequent HIV exposure, [69][70][71] in exposed uninfected infants with strong HIV-1-specific T cell responses, 72 and more recently in discordant couples 73 suggest that recurrent viral exposure may lead to priming of HIV-specific systemic and mucosal immune responses. These findings suggest that persons receiving PrEP who are exposed to HIV may generate HIV-specific T cell responses, potentially contributing to protection against the establishment of HIV infection.…”
Section: Mucosal Exposure In the Absence Of Chronic Infection Can Indmentioning
confidence: 99%